Synthesis of novel book-like K0.23V2O5 crystals and their electrochemical behavior in lithium batteries. Issue 83 (4th September 2015) - Xu, Maowen; Han, Jin; Li, Guannan; Niu, Yubin; Liu, Sangui; Hou, Junke; Wang, Minqiang; Song, Jie; Li, Chang Ming
Abstract : A novel book-like K0.23 V2 O5 crystal is obtained by a simple hydrothermal method and is explored as a cathode material for Li-ion batteries for the first time. Abstract : A novel book-like K0.23 V2 O5 crystal is obtained by a simple hydrothermal method and is explored as a cathode material for Li-ion batteries for the first time. It exhibits a high reversible capacity (of ca. 244 mA h g −1 at a current density of 50 mA g −1 ), along with a good rate capability (80 mA h g −1 at a current density of 1800 mA g −1 ) and a good capacity retention (185.3 mA h g −1 after 100 cycles).